Quantum oscillators - Henri-Rousseau, Olivier; Blaise, Paul.; Wiley InterScience (Online service) (Hoboken, N.J. : Wiley, 2011)
'Quantum Oscillators is a valuable source of information and an excellent supplementary text in courses on spectroscopy of hydrogen-bonded systems, one of the unsolved problems of science. This reference provides a reasonable and accessible entrance to the difficult subject of nonequilibrium quantum mechanics and is a timely update of classical works while, at the same time, providing a comprehensive treatment of hydrogen bonding. Also included is an appendix that summarizes mathematical concepts needed to understand the basis of the theory'--
'The book is divided into four parts. The first part is devoted to the concepts of quantum mechanics the knowledge of which is necessary for a good understanding of the dynamics of quantum oscillator which may be damped, and deals with time independent quantum mechanics and time dependent quantum mechanics'--
Frontmatter -- Color Plates -- Basis Required for Quantum Oscillator Studies. Basic Concepts Required for Quantum Mechanics -- Basis for Quantum Approaches of Oscillators -- Quantum Mechanics Representations -- Simple Models Useful for Quantum Oscillator Physics -- Single Quantum Harmonic Oscillators. Energy Representation for Quantum Harmonic Oscillator -- Coherent States and Translation Operators -- Boson Operator Theorems -- Phase Operators and Squeezed States -- Anharmonicity. Anharmonic Oscillators -- Oscillators Involving Anharmonic Couplings -- Oscillator Populations in Thermal Equilibrium. Dynamics of a Large Set of Coupled Oscillators -- Density Operators for Equilibrium Populations of Oscillators -- Thermal Properties of Harmonic Oscillators -- Quantum Normal Modes of Vibration. Quantum Electromagnetic Modes -- Quantum Modes in Molecules and Solids -- Damped Harmonic Oscillators. Damped Oscillators -- Vibrational Spectroscopy. Applications to Oscillator Spectroscopy -- Appendix -- Index.
Includes bibliographical references and index.
Print version record.
Keywords: Harmonic oscillators; Spectrum analysis; Wave mechanics; Hydrogen bonding; Electronic books; Electronic resource